PUBLIC RELATION SEBAGAI STRATEGI PENINGKATAN CITRA PEMERINTAH KOTA PAREPARE - Supiana, Supiana (An-Nida : Jurnal Komunikasi Islam, 2025)
This study aims to explore the role and strategies of public relations in enhancing the image of the Parepare City Government. The research adopts a qualitative approach utilizing SWOT analysis. The informants in this study consist of the Head of the Public Communications Division (HKP) at the Parepare Communication and Information Agency (Kominfo) and the staff from the same division. These informants serve as key actors in the strategies aimed at improving the city government's image, with the Head of the division responsible for idea generation and the public relations staff tasked with implementation. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing. The findings reveal several key roles of public relations in enhancing the image of the Parepare City Government, including managing government work programs, publicizing these programs, conducting news analysis, and evaluating public responses to government initiatives. Public relations strategies identified in this study include collaboration with local media, information campaigns, public dialogues, proactive communication and reputation management, as well as advertising and media partnerships. Government activities are predominantly publicized through online media, which has contributed significantly to fostering a positive image. Additionally, active interaction with the public and attention to their aspirations reflect efforts to create harmonious two-way communication, making development programs more relevant and effective in improving the welfare of society.